2017
DOI: 10.17576/jkmjc-2017-3303-14
|View full text |Cite
|
Sign up to set email alerts
|

Online Communication and Sustainability Reporting: The Managerial Issues

Abstract: The use of online communication to disclose sustainability efforts is becoming widespread especially in the technological advancement era. It involves communicating any sustainability related information via the internet, particularly on websites. There are managerial issues associated with the initiative use of online communication for sustainability reporting, even though it brings many benefits to companies in terms of increased transparency, reputation, trust, information accuracy, faster information disse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…Sustainability disclosure covers information related to economic, environmental, social and governance performance to stakeholders (Rahim and Omar, 2017). The lack of sustainability disclosure can be understood as evidence of a company' poor condition and thus negatively impact the decisions taken by stakeholders (Joshi and Gao, 2009).…”
Section: Background 21 Disclosing Sustainability Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustainability disclosure covers information related to economic, environmental, social and governance performance to stakeholders (Rahim and Omar, 2017). The lack of sustainability disclosure can be understood as evidence of a company' poor condition and thus negatively impact the decisions taken by stakeholders (Joshi and Gao, 2009).…”
Section: Background 21 Disclosing Sustainability Informationmentioning
confidence: 99%
“…Sustainability reporting via online communication, also designated by "online sustainability disclosure" (Amran et al, 2015). This type of disclosure refers to the communication of any sustainability-related information online via the Internet, particularly on websites (Rahim and Omar, 2017). In this paper, we use the term "sustainability" in the business context and "online sustainability disclosure" when referring to all type of corporate information about sustainability issues, including the corporate social responsibility, that is communicated by companies through their website The Internet has been developed as a key communication channel for disseminating corporate sustainability information since the late 1990s (Guthrie et al, 2008;Campbell, 2004).…”
mentioning
confidence: 99%
“…It is also important to form the plot about Wallace Story of Nature History and The World Spice Trail, the Magellan voyage, the Tordesillas Agreement and the Gold Glory and Gospel, extending up to the Flat Earth Issues. We also need to make sure about sustainability of online reporting (Nazahah, & Noorain, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The study employed Bursa CSR framework and RepTrak reputation model (Ponzi et al, 2011) to guide the study. The findings showed that CSR initiatives communicated via the corporate annual reports or sustainability reporting have a significant positive relationship with corporate reputation and firm performance (Rahim & Omar 2017). Gardberg, Zyglidopoulos, Symeou and Schepers (2017) examined the corporate philanthropy on reputation to enhance corporate social performance (CSP).…”
Section: Related Past Studies Of Social Responsibility and Corporate mentioning
confidence: 99%